Ambiente laboral en la satisfacción de los trabajadores de la Cooperativa de Ahorro y Crédito “Guaranda LTDA” Matriz Guaranda, provincia Bolívar año 2024. - Naranjo González Melanee Solange (2025)
The research titled “Work Environment and Employee Satisfaction at the ‘Guaranda Ltda.’ Savings and Credit Cooperative, Main Office Guaranda, Bolívar Province, Year 2024” aims to determine the factors related to the work environment that affect employee satisfaction. Through a descriptive and quantitative approach, the current conditions of satisfaction, relevant work factors, and their impact on employee performance and well-being were identified. The results show that while the physical conditions of the work environment are adequate, there are critical aspects that need strengthening, such as motivation, recognition, and opportunities for professional development. Additionally, challenges in internal communication and the balance between work and personal life were detected. In conclusion, the work environment plays a fundamental role in employee satisfaction, impacting their productivity and organizational commitment. It is recommended to implement policies focused on strengthening motivation, promoting recognition spaces, and professional development, with the aim of fostering a more positive and efficient work environment. Keywords: Work environment, job satisfaction, motivation, internal communication, productivity.